2003
DOI: 10.1159/000072451
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I Inactivation by Reticulol and Its in vivo Cytotoxicity against B16F10 Melanoma

Abstract: To investigate the enzyme-inhibitory efficacy and the cytotoxicity of reticulol produced from a strain of Streptoverticillium, we conducted a DNA topoisomerase (Topo) cleavage assay and an in vivo assay using B16F10 melanoma. From the inhibition assay of reticulol for Topo I, which is involved in melanoma metastasis, it was seen that Topo I treated with 45 µM reticulol did not replicate or transcribe DNA by forming supercoiled DNA. In the annexin V/propidium iodide staining assay to investigate the death patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In line with this argument, flavanonal silybin exhibited much weaker topo I inhibitors than flavonolignan DHS, and this correlates with a lack of ⌬ ⌿ m loss and DNA%SubG1 induction by silybin. Our results showed that DHS caused inhibition of topo I activity in both extractable and purified topo I at approximately 20-30 M , which are consistent with those reported for other topo I inhibitors [25] .…”
Section: Discussionsupporting
confidence: 91%
“…In line with this argument, flavanonal silybin exhibited much weaker topo I inhibitors than flavonolignan DHS, and this correlates with a lack of ⌬ ⌿ m loss and DNA%SubG1 induction by silybin. Our results showed that DHS caused inhibition of topo I activity in both extractable and purified topo I at approximately 20-30 M , which are consistent with those reported for other topo I inhibitors [25] .…”
Section: Discussionsupporting
confidence: 91%
“…Some chromenone derivatives have proven to be antimicrobial, anticancer, antioxidant and anti-inflammatory, anti-HIV, and anticoagulant agents. Typical examples include reticulol (Scheme ), described as a potent inhibitor of cyclic nucleotide phosphodiesterase, a topoisomerase I inactivator and an inhibitior of lung metastasis . In addition, capillarin (Scheme ), which contains a propargyl group at the 3-position of the heterocyclic ring, shows a potent antifungal activity .…”
Section: Introductionmentioning
confidence: 99%